Alterations in infant gut microbiome composition and metabolism after exposure to glyphosate and Roundup and/or a spore-based formulation using the SHIME technology. (26th July 2022) - Mesnage, Robin; Calatayud, Marta; Duysburgh, Cindy; Marzorati, Massimo; Antoniou, Michael N.
Abstract: Despite extensive research into the toxicology of the herbicide glyphosate, there are still major unknowns regarding its effects on the human gut microbiome. We describe the effects of glyphosate and a Roundup glyphosate-based herbicide on infant gut microbiota using SHIME technology. SHIME microbiota culture was undertaken in the presence of a concentration of 100-mg/L glyphosate and the same glyphosate equivalent concentration of Roundup. Roundup and to a lesser extent glyphosate caused an increase in fermentation activity, resulting in acidification of the microbial environment. This was also reflected by an increase in lactate and acetate production concomitant to a decrease in the levels of propionate, valerate, caproate and butyrate. Ammonium production reflecting proteolytic activities was increased by Roundup exposure. Global metabolomics revealed large-scale disturbances, including an increased abundance of long-chain polyunsaturated fatty acids. Changes in bacterial composition measured by qPCR and 16S rRNA suggested that lactobacilli had their growth stimulated as a result of microenvironment acidification. Co-treatment with the spore-based probiotic formulation MegaSporeBiotic reverted some of the changes in short-chain fatty acid levels. Altogether, our results suggest that glyphosate can exert effects on human gut microbiota.